Energy Efficiency and Directed Technical Change: Implications for Climate Change Mitigation - Gregory P. Casey (Center for Economic Studies and ifo Institute (CESifo), 2022)
I build a quantitative model of economic growth that can be used to evaluate the impact of environmental policy interventions on final-use energy consumption, an important driver of carbon emissions. In the model, energy demand is driven by directed technical change. Energy supply is subject to increasing extraction costs. The model is consistent with aggregate evidence on energy use, efficiency, and prices in the United States, as well as the standard balanced growth facts. I use the model to conduct several policy analyses. First, I examine the impact of energy taxes and compare the results to the standard Cobb-Douglas approach used in the environmental macroeconomics literature. Second, I investigate how the government can use energy taxes and R&D policy to implement the least-cost path that achieves an environmental target. Finally, I study the dynamic impacts of exogenous improvements in energy efficiency and R&D subsidies for energy efficiency, focusing on the role of rebound. All analyses highlight the importance of transition dynamics.
Keywords: H23; O33; O44; Q43; Q55; 330; energy; climate change; directed technical change; growth